Functional and Constraint Logic Programming 19th International Workshop, WFLP 2010, Madrid, Spain, January 17, 2010. Revised Selected Papers - Marino, Julio (Theoretical Computer Science and General Issues,, 2011)
This book contains a selection of the papers presented at the 19th International Workshop on Functional and Constraint Logic Programming, WFLP 2010, held in Madrid, Spain, in January 2010, as part of the ACM-SIGPLAN Principles of Programming Languages event, POPL 2010. From the 15 papers submitted, 12 were accepted for presentation at the workshop. The 8 regular papers presented in this volume were selected following a second round of reviewing, which took place after the event. They are complemented  by a full-length invited talk by the workshop's guest speaker, Mariangiola Dezani-Ciancaglini. All current issues in the areas of functional and constraint logic programming are covered including foundational aspects, language design, implementation, transformation and analysis, software engineering, integration of paradigms, and applications.